2009
DOI: 10.4296/cwrj3404441
|View full text |Cite
|
Sign up to set email alerts
|

An Evaluation of Mitigation Measures to Reduce Impacts of Peat Harvesting on the Aquatic Habitat of the East Branch Portage River, New Brunswick, Canada

Abstract: Abstract:The evaluation of impacts of peat harvesting on riverine ecosystems is essential to the implementation of adequate mitigation measures. The objective of the present study was to determine the potential impacts of peat harvesting on the physical (e.g., flow, suspended sediment concentration (SSC), water temperature) and biological (fish abundance) parameters of the East Branch Portage River, New Brunswick. This study was initiated in 2005 and a before and after study design was used to assess impacts. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 13 publications
0
8
0
Order By: Relevance
“…Wetlands in general can be prolific sources of aquatic biodiversity among all the biotic groups we use as bioindicators, but the literature on the impacts of boreal peat mining on aquatic biodiversity is limited and is mostly focused on semiaquatic or bog plants (Table 6). Only one study was found that assessed the effects of peat drainage on fish and it was inconclusive, although there was some indication of reduced abundance (Clement et al 2009). We found five studies that assessed the effects on amphibians and aquatic invertebrates, and all reported adverse effects to varying degrees (Table 6).…”
Section: Peat Miningmentioning
confidence: 99%
“…Wetlands in general can be prolific sources of aquatic biodiversity among all the biotic groups we use as bioindicators, but the literature on the impacts of boreal peat mining on aquatic biodiversity is limited and is mostly focused on semiaquatic or bog plants (Table 6). Only one study was found that assessed the effects of peat drainage on fish and it was inconclusive, although there was some indication of reduced abundance (Clement et al 2009). We found five studies that assessed the effects on amphibians and aquatic invertebrates, and all reported adverse effects to varying degrees (Table 6).…”
Section: Peat Miningmentioning
confidence: 99%
“…Peatland drainage ditches in New Brunswick (just outside the boreal zone in the hemiboreal subzone (sensu Brandt 2009)) delivered elevated concentrations of suspended sediments to downstream receiving waters, despite the use of sediment settling ponds in the peat mining area (Clément et al 2009). In a separate study, St-Hilaire et al (2006) also recorded elevated suspended sediment concentrations in downstream areas below sediment settling ponds of peat mining areas.…”
Section: Water Qualitymentioning
confidence: 99%
“…Most producers harvest peat using industrial vacuums, which requires that the living vegetation be removed from peatland and that the site be drained to improve drying and allow harvest of the superficial peat layer. The drainage waters are known to carry suspended sediments, both mineral (mostly clays) and organic (peat fiber), coming from surface and ditch erosion (Kløve, 1998;St-Hilaire et al, 2006, Clément et al, 2009Marttila and Klǿve, 2010). In Canada, best management practices require the installation of sedimentation basins to reduce the impact of suspended sediments on the receiving waters.…”
Section: Introductionmentioning
confidence: 99%
“…Two strategies are usually deployed to monitor SSC: intensive grab sampling, often with the help of auto-sampler (Marttila and Klǿve, 2008) or deployment of turbidity sensor capable of high frequency monitoring (Samson-Dô and St-Hilaire, 2018;Clément et al, 2009;Es-Salhi et al, 2013;Haahti et al, 2016;Pavey et al, 2007;St-Hilaire et al, 2006).…”
Section: Introductionmentioning
confidence: 99%